2017
DOI: 10.1038/lsa.2017.158
|View full text |Cite
|
Sign up to set email alerts
|

Giant intrinsic chiro-optical activity in planar dielectric nanostructures

Abstract: The strong optical chirality arising from certain synthetic metamaterials has important and widespread applications in polarization optics, stereochemistry and spintronics. However, these intrinsically chiral metamaterials are restricted to a complicated three-dimensional (3D) geometry, which leads to significant fabrication challenges, particularly at visible wavelengths. Their planar two-dimensional (2D) counterparts are limited by symmetry considerations to operation at oblique angles (extrinsic chirality) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
231
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(235 citation statements)
references
References 55 publications
2
231
0
2
Order By: Relevance
“…8 On the other hand, the need for an in-plane magnetic moment is eliminated for obliquely incident light, which is commonly termed as extrinsic chirality. 25,26 Recently though, Zhu et al 8 reported an experimental observation of a giant intrinsic chiroptical effect in an optically thin metasurface composed of a periodic array of chiral gammadion-shaped meta-atoms arranged on a dielectric slab. This metasurface selectively transmits only one spin state of light while diffracting the opposite spin.…”
Section: Introductionmentioning
confidence: 99%
“…8 On the other hand, the need for an in-plane magnetic moment is eliminated for obliquely incident light, which is commonly termed as extrinsic chirality. 25,26 Recently though, Zhu et al 8 reported an experimental observation of a giant intrinsic chiroptical effect in an optically thin metasurface composed of a periodic array of chiral gammadion-shaped meta-atoms arranged on a dielectric slab. This metasurface selectively transmits only one spin state of light while diffracting the opposite spin.…”
Section: Introductionmentioning
confidence: 99%
“…With tailored artificial subwavelength building blocks, metasurfaces are able to manipulate the local and far-field light, thus enabling a new generation of ultrathin optical elements with a broad range of functionalities [1][2][3][4][5][6][7][8]. By utilizing metasurfaces as information carriers, metasurface holograms are able to store and reconstruct full wave information of target objects.…”
Section: Introductionmentioning
confidence: 99%
“…Wavelength‐scale patterns of scatterers have shown the capability to produce bright colors and extravagant surface effects, often mocking what elegantly realized in biological systems . In particular, nanostructuration techniques, combined with powerful ab initio design tools, allow to develop materials which show a chiral response far larger than their natural counterparts, i.e., stereochemical compounds …”
mentioning
confidence: 99%